1977
DOI: 10.1002/1097-0142(197711)40:5+<2609::aid-cncr2820400933>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

The role of early diagnosis in controlling large bowel cancer.An overview

Abstract: Since early diagnosis is essential to improve the cure rate for large bowel cancer, we must use all known investigative tools to make a diagnosis in symptomatic patients in addition to periodic selective investigation of high-risk groups, such a8 those with familial polyposis, inflammatory bowel disease, previous polyps or cancer. However, our goal must be more ambitious than this. If we wait until patients have symptoms of colorectal cancer, the cure rate will significantly decrease. A mass-screening approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
29

Year Published

1980
1980
1987
1987

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 51 publications
0
2
0
29
Order By: Relevance
“…Studies are currently underway to determine whether testing for occult fecal blood loss is an effective screening device when applied to selected subgroups of the population [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. These studies assume that further diagnostic procedures are indicated in individuals who have fecal blood loss.…”
Section: Introductionmentioning
confidence: 99%
“…Studies are currently underway to determine whether testing for occult fecal blood loss is an effective screening device when applied to selected subgroups of the population [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. These studies assume that further diagnostic procedures are indicated in individuals who have fecal blood loss.…”
Section: Introductionmentioning
confidence: 99%
“…ορθού αποτελεί σήμερα ένα τεράστιο διεθνές πρόβλημα. 0 πρώτος λόγος είναι η συνεχής και ραγδαία αύξηση της συχνότητας της νόσου που παρατηρείται κατά τα τελευταία χρόνια στις αναπτυγ μένες, κύρια, χώρες (2,12,29,35,46,49,58,59,60,64,65,96,107,138,161,163) .…”
unclassified
“…Η αύξηση αυτή, τουλάχιστο μέχρι σήμερα, δεν παρουσιάζει τάση ανάκαμψης. Ο δεύτερος λόγος, που πρακτικά είναι και ο σπου δαιότερος, είναι ότι η 5ετής επιβίωση των αρρώστων που προσ βλήθηκαν απο την νόσο παραμένει κατά τα τελευταία 40 χρόνια σχεδόν στάσιμη (29, 49,60,64,65,96,113,138,141,156,163,166).…”
unclassified
See 2 more Smart Citations